Mean spore size and shape in ectomycorrhizal and saprotrophic assemblages show strong responses under resource constraints. (April 2017) - Halbwachs, Hans; Heilmann-Clausen, Jacob; Bässler, Claus
Abstract: Ectomycorrhizal and saprotrophic agaricoid basidiomycetes show diverse morphological reproductive traits, a phenomenon which has been attributed to their different lifestyles. From previous studies, we know that such differences are also reflected in assembly formation. Regardless of these differences, and assuming that dispersal fitness, predominantly by air movement, is one of the prevalent factors in fungal lifecycles, spores of both guilds should become on average more elongate and smaller with resource depletion. In our study we defined resource depletion as the decrease of living and dead organic biomass due to climate constraints along an elevational gradient in the Bavarian Forest (Germany). We found that spores of both guilds indeed become more elongate along the resource depletion gradient. Unexpectedly, the ectomycorrhizal assemblages showed larger spores under resource constraints, which could be a survivability trade-off. The spore trait syndrome responses to environmental constraints suggest ecological relevance, i.e. being advantageous in environments with patchily distributed resources. To deepen our mechanistic understanding of the underlying patterns, we particularly recommend experiments (artificial resource gradient free of confounding effects such as climate), and application of genomics and transcriptomics for elucidating the evolution of spore morphology. Highlights: Spores in fungal assemblages became more elongate with resource depletion. Dispersal fitness seems to be important for macrofungi under resource constraints. Ecto spores got larger with resource depletion, probably to improve survivability.